2019
DOI: 10.1634/theoncologist.2018-0868
|View full text |Cite
|
Sign up to set email alerts
|

An Eastern Hepatobiliary Surgery Hospital Microvascular Invasion Scoring System in Predicting Prognosis of Patients with Hepatocellular Carcinoma and Microvascular Invasion After R0 Liver Resection: A Large-Scale, Multicenter Study

Abstract: Background. Microvascular invasion (MVI) is associated with poor postoperative survival outcomes in patients with hepatocellular carcinoma (HCC). An Eastern Hepatobiliary Surgery Hospital (EHBH) MVI scoring system was established to predict prognosis in patients with HCC with MVI after R0 liver resection (LR) and to supplement the most commonly used classification systems. Materials and Methods. Patients with HCC with MVI who underwent R0 LR as an initial therapy were included. The EHBH-MVI score was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…Scholars have not yet come to a consensus regarding the prognostic factors of cHCC-CCA. Although previous studies have confirmed that microvascular invasion (MVI) is a prognostic factor for tumor recurrence and is associated with poor survival outcomes in HCC [11][12][13][14] and ICC [15,16], the relationship between prognosis and the presence of MVI in cHCC-CCA patients has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have not yet come to a consensus regarding the prognostic factors of cHCC-CCA. Although previous studies have confirmed that microvascular invasion (MVI) is a prognostic factor for tumor recurrence and is associated with poor survival outcomes in HCC [11][12][13][14] and ICC [15,16], the relationship between prognosis and the presence of MVI in cHCC-CCA patients has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, about half of the HCC patients suffer from postoperative recurrence in a few years, resulting in surgical failure and poor prognosis (3). Microvascular invasion (MVI) is a histopathologic evidence of local aggression and is considered as a strong predictor of postoperative recurrence in HCC (3)(4)(5)(6). Based on the above research evidences, the 2017 Guidelines for Diagnosis and Treatment of Liver Cancer in China have required the HCC pathological diagnosis to supply the description of MVI status based on pathological examination and necessary immunohistochemical staining (7).…”
Section: Introductionmentioning
confidence: 99%
“…For large HCC, tumor burden could have a more signi cant function in determining the OS compared to the liver function. Microvascular invasion (MVI) is a critical risk factor for HCC prognosis [33][34][35]. Previous studies demonstrated that the incidence of MVI increased with tumor size [36].…”
Section: Discussionmentioning
confidence: 99%